The Influence of Sharenting Behavior on Children's Privacy in Bandung City - Syam Maella, Nur’annafi Farni; Maharani Yasmin Diningrum; Siti Nursanti; Sholehah (IJESS International Journal of Education and Social Science, 2023)
Parents feel the need to share moments of their children's lives with family and friends via social media. Especially regarding their success in raising children, they need validation from other people. So parents in the city of Bandung do not hesitate to sharenting by utilizing various platforms on social media. Parents have freedom of expression, but each child also has privacy that must be protected because the other side of sharenting can have negative impacts. This research will examine the influence of sharenting behaviors carried out by parents on children's privacy. The research method used was quantitative, with the statistical tests used being the linear regression test and the F test. The research was conducted with 100 parents in the city of Bandung. The results of the hypothesis test show that sharenting behavior (variable X) simultaneously influences children's privacy (variable Y). This is proven by the calculated F value of 44.931, which is greater than the F table of 6.010. Thus, a significant value of 0.000 is also obtained, which is lower than the probability limit of 0.05.